Efektivitas Badan Usaha Milik Desa (BUMDES) dalam Meningkatkan Pendapatan Asli Desa di Desa Kutuh Kecamatan Kuta Selatan Kabupaten Badung - Wati, Kadek Sukma; Wijaya, Komang Adi Sastra; Winaya, I Ketut (CITIZEN CHARTER; Vol 2 No 1 (2022): Administrasi Publik 2022, 2022)
Kutuh Village is one of the villages in South Kuta District, Badung Regency which has succeeded in establishing BUMDes on October 30, 2016 under the name BUMDes Manik Sedana Kutuh. BUMDes Kutuh was established based on Village Regulation Number 5 of 2016 concerning the Establishment of Village-Owned Enterprises. BUMDes Kutuh's efforts to increase village original income are by establishing three work programs, namely the Pancali Spa business unit, the waste transportation service unit, and the goods and services business unit which currently still has problems.This research uses a qualitative research type with a descriptive approach. Based on this research study using the theory of effectiveness by Masruri (2014). The results of the study show that the effectiveness of BUMDes in increasing village original income in Kutuh Village is quite good but not effective as a whole. Keywords: Effectiveness, Village Owned Enterprises (BUMDes), Village Original Income